Multidonor FMT capsules improve symptoms and decrease fecal calprotectin in ulcerative colitis patients while treated – an open-label pilot study. (4th March 2019) - Cold, F.; Browne, P. D.; Günther, S.; Halkjaer, S. I.; Petersen, A. M.; Al-Gibouri, Z.; Hansen, L. H.; Christensen, A. H.
Abstract: Background: Growing evidence indicates that gut dysbiosis is a factor in the pathogenesis of ulcerative colitis (UC). Fecal microbiota transplantation (FMT) appears to be promising in inducing UC remission, but there are no reports regarding administration using capsules. Methods: Seven patients with active UC, aged 27–50 years, were treated with 25 multidonor FMT capsules daily for 50 days as a supplement to their standard treatment in an open-label pilot study. The primary objective was to follow symptoms through the Simple Clinical Colitis Activity Index (SCCAI). Secondary objectives were to follow changes in fecal calprotectin and microbial diversity through fecal samples and quality of life through the Inflammatory Bowel Disease Questionnaire (IBDQ). Participants were followed through regular visits for six months. Results: From a median of 6 at baseline, the SCCAI of all participants decreased, with median decreases of 5 ( p  = .001) and 6 ( p  = .001) after 4 and 8 weeks, respectively. Three of the seven patients had flare-up/relapse of symptoms after the active treatment period. The median F-calprotectin of ≥1800 mg/kg at baseline decreased significantly during the treatment period, but increased again in the follow-up period. The median IBDQ improved at all visits compared to baseline. The fecal microbiota α-diversity did not increase in the study period compared to baseline. All participants completed the treatment and no serious adverse events were reported. Conclusion: Fifty days of daily multidonor FMT capsules temporarily improved symptoms and health-related life quality and decreased F-calprotectin in patients with active UC.